Implant risk failure in patients undergoing postmastectomy 3-week hypofractionated radiotherapy after immediate reconstruction. (October 2021) - Rojas, Damaris Patricia; Leonardi, Maria Cristina; Frassoni, Samuele; Morra, Anna; Gerardi, Marianna Alessandra; La Rocca, Eliana; Cattani, Federica; Luraschi, Rosa; Fodor, Cristiana; Zaffaroni, Mattia; Rietjens, Mario; De Lorenzi, Francesca; et al.
Highlights: A growing number of patients is being treated with postmastectomy radiotherapy. The number of patients with implant-based breast reconstruction is increasing. The optimal timing and sequence of reconstruction and radiotherapy is unanswered. Hypofractionation has been gaining ground in implant-based breast reconstruction radiotherapy. Abstract: Aim: To evaluate reconstruction failure (RF) rate in patients receiving implant-based immediate breast reconstruction (IBR) and hypofractionated (HF) postmastectomy radiation therapy (PMRT). Materials and methods: Stage II–III breast cancer patients, treated with HF-PMRT using intensity modulated radiotherapy were stratified in two groups according to IBR: single-stage direct-to-implant (DTI-group) and two-stage expander and implant (TE/I-group). Irradiated patients were matched with non-irradiated ones who underwent the same IBR during the same period. Prescription dose was 40.05 Gy/15 fractions to chest wall and infra/supraclavicular nodal region. Primary endpoint was RF defined as the need of major revisional surgery (MaRS) for implant removal or conversion to autologous reconstruction. Secondary endpoint was the rate of minor revisional surgeries (MiRS) including implant repositioning or substitution with another implant. Results: One hundred and seven irradiated patients (62 in TE/I-group, 45 in DTI-group) were matched with 107 non-irradiated subjects. Median follow-up was 4.2 years (0.1–6.1) In the TE/I setting, MaRS was performed in 8/62 irradiated patients (12.9%) of the irradiated TE/I group compared to 1/62 (1.6%) non-irradiated subjects ( p  = 0.015). In the DTI setting, MaRs occurred in 3/45 irradiated patients (6.7%) compared to 1/45 non-irradiated ones (2.2%) ( p  = 0.35). Overall MaRS rate was 10.3% in the irradiated group. MiRS was performed in 35.6% and 31.1% of the irradiated and non-irradiated DTI-groups ( p  = 0.65), respectively, and in 12.9% and 8.1% of the irradiated and non-irradiated TE/I groups ( p  = 0.38), respectively. Conclusions: Compared to the non-irradiated counterparts, the TE/I group showed higher rate of RF, while no statistically significant difference was observed for the DTI group. The use of hypofractionation and IMRT to implant-based IBR did not seem to increase the risk of RF which appeared to be in line with the literature